Further Evaluations of Functional Communication Training and Chained Schedules of Reinforcement to Treat Multiple Functions of Challenging Behavior. (November 2013) - Falcomata, Terry S.; Muething, Colin S.; Gainey, Summer; Hoffman, Katherine; Fragale, Christina
We evaluated functional communication training (FCT) combined with a chained schedule of reinforcement procedure for the treatment of challenging behavior exhibited by two individuals diagnosed with Asperger syndrome and autism. Following functional analyses that suggested that challenging behavior served multiple functions for both participants, we implemented FCT in which mands for a discriminative stimulus (S D ; wristband) were reinforced with access to the S D and all three functional reinforcers. Next, we modified the procedure by incorporating delays to increase ease of implementation and promote toleration of delays to reinforcement. Last, we made additional modifications to the procedure by incorporating a chained schedule of reinforcement such that (a) mands for the wristband were reinforced with access to the wristband and (b) specific mands for respective functional reinforcers were reinforced in the presence of the wristband. The results showed that the procedure successfully treated challenging behavior with multiple functions. Future directions in the evaluation and development of treatments that simultaneously address multiple functions are discussed.